Faktor-Faktor Penggunaan Sistem RFID di Sektor Perindustrian di Selangor - Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2023)
Radio Frequency Identification (RFID) is one of the wireless technologies. RFID technology is widely used in a variety of industries and can be practiced in various sectors. However, there are some industries that are experiencing problems and difficulties in the use of RFID systems due to several factors. Therefore, this study aims to identify the level of knowledge of the use of RFID technology systems. In addition, this study was also conducted to identify the weighting factors that affect the use of RFID technology in the industrial sector in the Selangor Darul Ehsan area. Research data was obtained through a survey form from employees at companies registered under the Malaysian Technology Development Corporation (MTDC). Quantitative methods through the Statistical Package for The Social Science (SPSS) and the Analytical Hierarchy Process (AHP) method were used to analyze data in achieving the objectives of the study. The results of the study found that companies registered under MTDC have a high level of knowledge of the use of RFID technology. In addition, the information intensity factor has a high weighting in the use of RFID technology among companies registered under the MTDC.